Retrospective Data Analysis of the Influence of Age and Sex on TPMT Activity and Its Phenotype–Genotype Correlation. (1st March 2019) - Wu, Fang; Melis, Roberta; McMillin, Gwendolyn A; Johnson-Davis, Kamisha L
Abstract: Background: Therapeutic efficacy and toxicity of thiopurine drugs (used as anticancer and immunosuppressant agents) are affected by thiopurine S-methyltransferase (TPMT) enzyme activity. TPMT genotype and/or phenotype is used to predict the risk for adverse effects before drug administration. Inosine triphosphate pyrophosphatase (ITPA) is another enzyme involved in thiopurine metabolism. In this study, we aimed to evaluate ( a ) frequency of various TPMT phenotypes and genotypes, ( b ) correlations between them, ( c ) influence of age and sex on TPMT activity, and ( d ) distribution of ITPA variants among various TPMT subgroups. Methods: TPMT enzyme activity was determined by LC-MS/MS. TPMT (*2, *3A–C) and ITPA (rs1127354, rs7270101) genotypes were determined using a customized TaqMan ® OpenArray ® . Results: TPMT enzyme activity varied largely (6.3–90 U/mL). The frequency of low, intermediate, normal, and high activity was 0.5% (n = 230), 13.1% (n = 5998), 86.1% (n = 39448), and 0.28% (n = 126), respectively. No significant difference in TPMT activity in relation to age and sex was found. Genotype analysis revealed the frequency of variant TPMT alleles was 6.73% (*3A, n = 344), 0.05% (*3B, n = 2), 2.22% (*3C, n = 95), and 0.42% (*2, n = 19). Analysis of paired phenotype and genotype showed that TPMT activity in samples with variant allele(s) was significantly lower than those without variant alleles. Lastly, an equal distribution of ITPA variants was found among normal and abnormal TPMT activity. Conclusions: This retrospective data analysis demonstrated a clustering of variant TPMT genotypes with phenotypes, no significant influence of age and sex on TPMT activity, and an equal distribution of ITPA variants among various TPMT subgroups.